'Vilain et deshonneste': Anti-Politique Polemic at the End of the Wars of Religion. Issue 2 (3rd July 2017) - Claussen, Emma
Abstract : This article approaches the theme of villainy in two ways. It looks at the vilification of a figure named politique in two pro- Ligue pamphlets printed in Paris in 1589. Within this, the word vilain is deployed as one of several clustered insults used in the process of vilification. I discuss the problems of meaning associated with these word uses which seem primarily intended to insult, wound, and to vilify supporters of the Valois (and then Bourbon) monarchy, and ask whether vilain has any particular significance, or even 'content', in these texts. I use a methodological framework that employs linguistic theories of contextually derived meaning, and literary approaches that privilege analysis of particular 'key' words, to explore the meeting of the words politique and vilain in a continuum between 'meaningless' hate speech and 'meaningful' socio-political commentary.